Inovasi gadget: menelusuri dampaknya terhadap kalangan anak muda - Lazuardhi, Alex Febryan (Maliki Interdisciplinary Journal, 2025)
Technological development in the modern era has advanced rapidly, impacting nearly all aspects of human life, including communication, industry, agriculture, and education. One prominent manifestation of this progress is the gadget, which has become an essential part of daily life. Gadgets not only facilitate long-distance communication but also provide access to information, economic opportunities, and ease in teaching and learning processes. However, these advancements also bring negative impacts, such as addiction, health issues, and reduced social interaction, especially among children and adolescents. Therefore, it is crucial to use gadgets wisely and in a balanced manner, with active involvement from parents, teachers, and communities in providing education and supervision. The future of gadgets is promising if they are developed and utilized positively, supported by innovation from youth who uphold ethics and morality.